ANXIETY IN ANDREA BERLOFF'S WORLD TRADE CENTRE: A PSYCHOANALYTIC APPROACH - WIBOWO, M. HADI (2010)
The study is to reveal how the struggle for better life of the major character, John McLoughlin, influences his personality. The objective of the study is to analyze the movie based on the structural analysis and the psychoanalytic analysis. This study is a qualitative study. The object of the study is Andrea Berloff's World Trade Centre. The data sources are divided into two, namely primary data source and secondary data source. In collecting the data, the writer watches the movie and uses library research by collecting and selecting the appropriate data from many sources. The technique of the data analysis, the writer uses descriptive technique. After analyzing the movie of Andrea Berloff's World Trade Centre, the writer concluded that there are several aspects of psychoanalytic approach of the major character. The aspects consist of id, ego and superego. The anxieties of the major character consist of reality anxiety, neurotic anxiety, and moral anxiety. . The conflict of the three elements of John McLoughlin personality occurs, influencing his mental condition and causing his anxiety. Anxiety attacks him when he is in a complicated situation and it forces the ego to make decision between the conflicts o the id and the superego. The cause of his anxiety comes from the situation that threats him and puts him in dangerous and deadly situation.